PENDIDIKAN INKLUSIF (Mewujudkan Keadilan, Kesetaraan Dalam Lingkungan Multikultural) - Wahid, Annisa; Khoulita, Ikfi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Inclusive education is an educational approach that aims to create justice and equality in a multicultural environment. This research aims to analyze the importance of inclusive education in achieving justice and equality amidst an increasingly diverse cultural and ethnic society. This study uses the library method using qualitative research typeso obtained from journal, articles and books related to the object of research. The results of this study indicate inclusive education brings significant benefits to individuals and society as a whole. In an inclusive environment, individuals with differences in abilities or disabilities can learn alongside their peers, resulting in mutual understanding, tolerance, and friendship. Moreover, inclusive education reduces stigmatization and discrimination, enabling individuals to fully contribute to a fair and equal society. To achieve inclusive education, collaborative efforts from all stakeholders are required. The education system needs to make changes in policies, teaching practices, and assessments to ensure fair recognition and access for all individuals. Inclusive education also requires ongoing training and development for teachers and school staff to be able to meet the diverse needs of learners.